A descriptive and comparative neurocranium morphology of Anguilliformes fishes in Taiwan waters - Ramos-Castro, Marites; Loh, Kar-Hoe; Chen, Hong-Ming (Zootaxa, 2021)
Taiwan is one of the richest in the world in terms of eel fauna. In this study, we examined the osteological and morphological characteristics of eels under order Anguilliformes. Furthermore, we focused on the neurocranium of total of 30 Anguilliformes fishes under family Congridae (10), Muraenesocidae (1), Muraenidae (7), Nemichthyidae (1), Nettastomatidae (2), Ophichthidae (5), Synaphobranchidae (4), which are caught in Taiwanese waters. This paper shows the results of a comparative study on osteological characters of the neurocranium including the ratio of seven length characters using its NCL (neurocranium length), NCW (neurocranium width), OBL (orbit length), MFW (maximum frontal width), NCDB (neurocranium depth at basisphenoid), PEVW (premaxilla-ethmovomer width) and mPOBL (mid pre-orbital length), and 20 morphological diagnostic characters for 30 eel species. Results shows that species under family Nemichthyidae and Nettastomatidae have the highest values on the ratio of NCL/MFW, NCL/NCDB, and NCW/mPOBD. In morphological characters, it shows that species of the same family mostly share similar formation of the PEV plate and frontal structure. The usage of the length measurements and morphological diagnostic characters of neurocranium allowed for a more in depth understanding of how similar or different these eels can be. The neurocranial description and morphological characters may prove valuable for identification purposes and might be necessary tool for further studies on the status of order Anguilliformes.